Pengaruh Penggunaan Media Berbasis Information and Communication Technology (ICT) terhadap Hasil Belajar Siswa pada Materi Dimensi Tiga - Djihad Wungguli; Lailany Yahya (Department of Mathematics, Universitas Negeri Gorontalo, 2020)
These paper have purposed to know the difference of result between the students that have learned by using IT and the students who had subject follow by using conventional learning method in dimension three subject. The research method used in this study is an experimental method using Posttest-Only Control Group Design. The results showed that the average learning outcomes of students who get learning by using ICT media is higher than the average learning outcomes of students who get learning by using conventional learning models on the three-dimensional material.